Patterns of Pupillary Activity During Binocular Disparity Resolution - Balaban, Carey D.; Kiderman, Alex; Szczupak, Mikhaylo; Ashmore, Robin C.; Hoffer, Michael E. (Frontiers in Neurology, 2018)
This study examined the dynamic coordination between disconjugate, vergence eye movements and pupil size in 52 normal subjects during binocular disparity stimulation in a virtual reality display. Eye movements and pupil area were sampled with a video-oculographic system at 100 Hz during performance of two tasks, (1) fusion of a binocular disparity step (±1.5 degrees of visual angle in the horizontal plane) and (2) pursuit of a sinusoidally varying binocular disparity stimulus (0.1 Hz, ±2.6 degrees of visual angle in the horizontal plane). Pupil size data were normalized on the basis of responses to homogeneous illumination steps ranging from 0.42 to 65.4 cd/m ². The subjects produced robust vergence eye movements in response to step disparity shifts and high fidelity sinusoidal vergence responses (R2 re: stimulus profile: 0.933 ± 0.088), accompanied by changes in pupil area. Trajectory plots of pupil area as a function of vergence angle showed that the pupil area at zero vergence is altered between epochs of linear vergence angle – pupil area relations. Analysis with a modified Gath-Geva clustering algorithm revealed that the dynamic relationship between the ocular vergence angle and pupil size includes two different transient, synkinetic response patterns. The near response pattern, pupil constriction during convergence and pupil dilation during divergence, occurred approximately 80% of the time across subjects. An opposite, previously undescribed synkinetic pattern was pupil constriction during divergence and pupil dilatation during convergence; it occurred approximately 15% of the time across subjects. The remainder of the data were epochs of uncorrelated activity. The pupil size intercepts of the synkinetic segments, representing pupil size at initial tropia, had different relationships to vergence angle for the two main coordinated movement types. Hippus-like movements of the pupil could also be accompanied by vergence movements. No pupil coordination was observed during a conjugate pursuit task. In terms of the current dual interaction control model (1), findings suggest that the synkinetic eye and pupillary movements are produced by a dynamic switch of the influence of vergence related information to pupil control.